2021
DOI: 10.1021/acsami.0c22677
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a Low-Voltage, High-Mobility IGZO Transistor through an ALD-Derived Bilayer Channel and a Hafnia-Based Gate Dielectric Stack

Abstract: Ultrahigh-resolution displays for augmented reality (AR) and virtual reality (VR) applications require a novel architecture and process. Atomic-layer deposition (ALD) enables the facile fabrication of indium–gallium zinc oxide (IGZO) thin-film transistors (TFTs) on a substrate with a nonplanar surface due to its excellent step coverage and accurate thickness control. Here, we report all-ALD-derived TFTs using IGZO and HfO2 as the channel layer and gate insulator, respectively. A bilayer IGZO channel structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
84
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 68 publications
0
84
1
Order By: Relevance
“…The µ sat of the device is larger (33.76 cm 2 V −1 s −1 ), but the I on /I off (1.96 × 10 7 ) and ∆V th (0.3 V) are not as good as our results [24]. Min Hoe Cho et al reported a bilayer IGZO TFT, consisting of a 10 nm base layer (In 0.52 Ga 0.29 Zn 0.19 O) with good stability and a 3 nm boost layer (In 0.82 Ga 0.08 Zn 0.10 O) with extremely highest mobility (74.0 ± 0.91 cm 2 V −1 s −1 ) [13]. As mentioned above, rich a-IGZO films will produce uncontrollable conductivity in the channel layer so that the film mobility is greatly improved.…”
Section: Zr-doped Hfo 2 Dieletricscontrasting
confidence: 82%
See 2 more Smart Citations
“…The µ sat of the device is larger (33.76 cm 2 V −1 s −1 ), but the I on /I off (1.96 × 10 7 ) and ∆V th (0.3 V) are not as good as our results [24]. Min Hoe Cho et al reported a bilayer IGZO TFT, consisting of a 10 nm base layer (In 0.52 Ga 0.29 Zn 0.19 O) with good stability and a 3 nm boost layer (In 0.82 Ga 0.08 Zn 0.10 O) with extremely highest mobility (74.0 ± 0.91 cm 2 V −1 s −1 ) [13]. As mentioned above, rich a-IGZO films will produce uncontrollable conductivity in the channel layer so that the film mobility is greatly improved.…”
Section: Zr-doped Hfo 2 Dieletricscontrasting
confidence: 82%
“…The ∆V th and ∆SS are 0.09 V and 0.057 V/dec after 10 4 s PBST, respectively, illustrating the long-term stability, excellent electrical characteristics device for a wide perspective application. [13] 0.2 74.0 3 × 10 8 0.17 1.9 × 10 11 0.66…”
Section: Zr-doped Hfo 2 Dieletricsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Finally, the high-mobility, low-driving-voltage IGZO TFTs by adopting bilayer channel and hafnia-based gate dielectric stack were investigated. [10] Figure 1. Required field-effect mobility to satisfy the trend towards ultra-high-definition and high frame rate driving in the next generation flat-panel displays.…”
Section: Introductionmentioning
confidence: 99%
“…Summary of the electrical parameters of the base-layer IGZO TFTs with different gate insulator. Data adapted from reference[10].…”
mentioning
confidence: 99%